Financing of small business - What factors influencing the bankers' credit evaluation? - Mahmood, Rosli (Universiti Utara Malaysia, 1995)
Small business are always at a disadvantage and facing difficulties in obtaining loans due to perceived high risks and costs. Furthermore, they do not have access to other financial markets due to their size, and to much greater extent must rely on conventional banks for financing. This study conducted among the commercial banks and finance companies in Malaysia reveals that the quality of management and default risks are the two most important factors the bankers look into before extending credit facilities to the small businesses.